Pulih Bersama Tumbuh Bersama: FGD Literasi Kesehatan Mental pada Ibu Rumah Tangga di Wilayah Kerja UPTD Puskesmas Tapos - Sobar Darmaja; Neneng Mukaffa Opier; Reza Anggun Putri Ambarwati; Adinda Riska Romadloniyah Putri; Putri Azzahra Azzahra; Erlya Zahra; Surlina Gulo; Suminingsih Suminingsih (Universitas Baiturrahim, 2026)
Mental health issues are critical concerns that significantly affect the quality of life of individuals and families. A preliminary study revealed low levels of mental health literacy among housewives in the working area of UPTD Puskesmas Tapos. This Community Field Practice II aimed to enhance mental health literacy among housewives through the Focus Group Discussion (FGD) method. The intervention was conducted on August 28, 2025, involving 15 participants aged 25–45 years. The media used included “Pohon Laras,” educational flipcharts, and the journaling book Ruang Pulih & Refleksi. Evaluation through pre test and post-test showed an increase in the average score from 7.8 to 9.2. A total of 93.3% of participants demonstrated improved understanding, with an average increase of 19.58%. These results indicate that participatory and educational approaches are effective in improving mental health literacy, reducing stigma, and encouraging housewives to practice simple self-care strategies at home.